Medication Overuse Headache and Its Specific Clinical Markers [Cefalea por Abuso de Medicamentos y Sus Marcadores Clínicos] - Barrientos-Uribe, N (Sociedad de Neurologia Psiquiatria y Neurocirugia, 2022)
Introduction: Clinical markers of medication overuse headache (MOH) are based on headache classification developed by the International Headache Society (IHS). This classification include only two criteria: frequency of headache days must be 15 or more days per month for at least three or more months; - and the number of days of overuse medication must be either 10 or 15 days per month depending on the type of medication. However, patients often have others distinct associated clinical markers, which are overlooked by most physicians during the initial evaluation. Methodology: This study is a prospective, longitudinal and observational study of 76 patients admitted to DIPRECA s hospital Headache Unit. They were all diagnosed with, MOH according to the criteria established by the his ICHD III beta.(1) Patients were given standard treatment including detoxification and preventive medications and followed for 6 months. Symptoms of interest were recorded in at each clinical monitoring visit and assessment scales such as Zung, MIDAS, HIT-6 were administered. Results: Overused medications included nonsteroidal anti-inflammatory drugs (NSAIDs), triptans and ergots. The most significant clinical symptoms associated were: awaking in the morning with headache, awaking the patient at dawn by headache, attention difficulties, depression, cervical pain and myofascial pain syndrome. All symptoms significantly improved when treatment began, as did quality of life as measured by MIDAS and HIT-6 scales. Discussion: In evaluating patients with MOH consider both the ICHD III beta diagnostic criteria and the common and specific symptoms seen in most cases of MOH. © 2022 Sociedad de Neurologia Psiquiatria y Neurocirugia. All rights reserved.